(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
It is since the Vedic era that the use of natural substances for medicine has been used. Ayurveda, the ancient Indian science gives a detailed explanation of these uses. Medicated milk i.e., Siddha ksheera has a high and prominent medicinal value. This article encloses all the various formulations of medicated milk along with their role in diseases contents of the medicated milk as per Acharya Charak. Ksheerpaka are supposed to nourish tissues and have more anabolic effects. An effort has been made to compile and represent for a better and easy understanding of various Siddha ksheer yogas mentioned in Charaka samhita. Use of Ksheer is highly recommended in certain Vyadhis like Pandu, Amlapitta, Gulma, Udara roga, Yoni roga, Shukra roga, Vata roga, etc. Ksheerpaka i.e. milk used in the medicated form is the unique feature of Ayurveda. Nowadays, for Ksheerpaka preparation, method stated by Sharangadhara is generally followed. Role of Siddha ksheer in various Vyadhis like Jwara, Raktapitta, Gulma, Rajyakshma, Kshata ksheen, Udar, Shotha has been mentioned in the article. Role of various Vanaspati dravyas to be used for preparing Siddha ksheer paka like Shatavari, Bala etc has also been mentioned. Use of Siddha ksheer for Rasayan and Vajikaran has been explained to help the reader to get a better and wider understanding about Siddha ksheer samkalpana and its role in various diseases.